Three parametric volume tables for forest management - Martinez Millan, F. J.; Ara Lazaro, P.; Gonzalez Doncel, I. (Forest Systems, 1992)
A set of volume equations are presented, providing the merchantable timber volume for the principal tree species, present at the Spanish managed forests. These equations allow to replace felled sampled trees, for the mensuration, on standing trees of d.b.h., diameter at 4 m over stump and total height. From these data, local volume tables for management, can be obtained.